2017
DOI: 10.1186/s40461-017-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying working and learning in vocational education: a multilevel investigation of emotional crossover and contextual moderators

Abstract: Background: Students' positive emotions, such as enjoying learning activities at school, are increasingly recognized as being conducive to learning. Researchers therefore seek to understand the roles that teachers' emotions and instructional behaviours play for promoting activity-related enjoyment among their students. This study is the first to investigate emotional crossover in vocational classrooms, combining ControlValue Theory and Broaden-and-Built Theory to substantiate potentially mediating teaching cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
7
2
Order By: Relevance
“…The findings of the study revealed non-significant relationships in respect of the crossover relationships proposed as well as the two indirect effects of student–LMX and lack of reciprocity as mediators in the crossover process. These findings were inconsistent with findings in similar previous research that showed crossover from the teacher/lecturer to the student through mediators such as enthusiastic teaching, clarity in teaching, 38 and emotional contagion. 32 The absence of statistically significant effects between lecturer and students gives the impression that crossover might depend on the context in which the instructional interaction takes place (eg, lecturer–student relationships during a global pandemic, which are characterised by remote or blended instructional interactions).…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the study revealed non-significant relationships in respect of the crossover relationships proposed as well as the two indirect effects of student–LMX and lack of reciprocity as mediators in the crossover process. These findings were inconsistent with findings in similar previous research that showed crossover from the teacher/lecturer to the student through mediators such as enthusiastic teaching, clarity in teaching, 38 and emotional contagion. 32 The absence of statistically significant effects between lecturer and students gives the impression that crossover might depend on the context in which the instructional interaction takes place (eg, lecturer–student relationships during a global pandemic, which are characterised by remote or blended instructional interactions).…”
Section: Discussioncontrasting
confidence: 99%
“…More concretely, and regarding the present study, teachers' competencies are related to cognitive activation (Baumert et al, 2010;Förtsch et al, 2016) and thus to the quality of teachers' feedback on student assignments and their promotion of students' self-regulation skills. Moreover, teachers' motivation tends to predict students' motivation (by means of supporting the development of competence and autonomy) (Frenzel et al, 2009;Holzberger et al, 2016;Warwas & Helm, 2017). Finally, there is ample evidence (feedback in this study; ) that instructional quality and students' motivation (Deci & Ryan, 1993) -as well as students' self-regulation -are related to students' academic achievement (Boekaerts & Corno, 2005;Schoor et al, 2015;Seidel & Shavelson, 2007).…”
Section: On the Relations Between Context Input Process And Output In...mentioning
confidence: 61%
“…The student's positive demeanour towards teacher is driven by a good relat ionship between the teacher and the student. The study carried out by Warwas and Helm (2017) found that, there exists a positive relationship between the characteristics of teaching executed by the teacher and the enjoyment of learning among the students. The positive relat ionship created by a teacher and his students is the most important aspect in encouraging positive development of the student and which will then be able to create a social environ ment which is more friendly and caring (Robert et al, 2012).…”
Section: Relationship Between Student and Teachermentioning
confidence: 99%